2022
DOI: 10.1111/jfbc.14142
|View full text |Cite
|
Sign up to set email alerts
|

Geraniol ameliorates the progression of high fat‐diet/streptozotocin‐induced type 2 diabetes mellitus in rats via regulation of caspase‐3, Bcl‐2, and Bax expression

Abstract: Diabetes mellitus (DM) is rapidly overburdening the world's healthcare systems. In parallel to globalization, marked disparities in human attitudes and lifestyles have contributed to diabetes rates escalating (Hasan & Mohieldein, 2016). In 2019, the International Diabetes Federation stated that about 463 million adults (20-79 years) worldwide were affected by DM (Cuschieri & Grech, 2020).Insufficient insulin production and/or lack of insulin sensitivity may be causing diabetes. Also, a sequence of chronic meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
1
4
1
Order By: Relevance
“…BAX, a well-recognized marker of apoptosis, is a pro-apoptotic protein that belongs to the Bcl-2 gene family. Similar to our findings, previous studies demonstrated a marked increase in BAX expression in cells lining glomeruli and renal tubules of diabetic rats using immunohistochemical analysis [ 66 , 67 ]. Previous research has shown that hyperglycemia causes mesangial cell death via oxidative stress and inflammation, marked by an increase in the BAX/Bcl-2 ratio [ 68 , 69 ].…”
Section: Discussionsupporting
confidence: 92%
“…BAX, a well-recognized marker of apoptosis, is a pro-apoptotic protein that belongs to the Bcl-2 gene family. Similar to our findings, previous studies demonstrated a marked increase in BAX expression in cells lining glomeruli and renal tubules of diabetic rats using immunohistochemical analysis [ 66 , 67 ]. Previous research has shown that hyperglycemia causes mesangial cell death via oxidative stress and inflammation, marked by an increase in the BAX/Bcl-2 ratio [ 68 , 69 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, researchers have shown that the activation of apoptotic factors caspase-8 and caspase-10 (inducers of the extrinsic pathway) and caspase-9 (inducers of the intrinsic pathway) are engaged in the activation of caspase-3 and apoptosis. 54 In the present study, AOM-treated rats had down-regulated Bax protein and up-surged Bcl-2 protein expressions but these effects were reversed when rats dieted with PN 30 and 60 mg/kg for 2 months. Accordingly, previous findings showed significant stimulatory potentials of PN in acute leukaemia cells by the augmentation of different intrinsic and extrinsic mechanisms via different apoptotic factors including pro-apoptotic protein (Bax) and death receptor (Fas).…”
Section: Discussioncontrasting
confidence: 41%
“…The second group (diabetic group, DC) was fed a HFD for eight weeks. In the third group, the rats received sub-cutaneous injections of insulin (2 U/rat) once daily for an 8-week period [ 36 ]. Group four (DKI) was the diabetic group and obtained 100 mg/kg of body weight of kiwi extract orally per day as a treatment.…”
Section: Methodsmentioning
confidence: 99%